Promoting the local development of disaster-affected communities - Razeto Pavez, Alicia Cristina (Revista INVI, 2013)
In this paper, we formulate a theoretical analysis to propose that the so-called “natural” disasters are in fact a social phenomena. Each phase of a disaster is analyzed so as to reveal the generation of social relationships and thus support this way to understanding them. As a consequence of this conceptualization, it is possible to see that policy responses to disasters do not only have to focus on reconstruction, but should include instruments that promote the development conditions of stricken areas. In line with this integral perspective to address disasters is the local development approach. The analysis of the latter provides five dimensions from which it is possible to contribute to the improvement of disaster-affected localities.